The phonological loop as a buffer store: An update. (March 2019) - Baddeley, Alan D.; Hitch, Graham J.
Abstract: We regard our multicomponent model of working memory as reflecting a hierarchy of buffer stores with buffer storage providing an effective way of combining information from two or more streams that may differ in either the speed of input or in the features coded. We illustrate this through the case of the phonological loop component of the model. We discuss its gradual development through a combination of evidence from mainstream cognition and neuropsychology with the need for more detailed modelling of issues such as the representation of serial order. A brief account follows of the application, beyond the laboratory and clinic, of the concept of a phonological loop and the methods designed to study it. We then discuss some criticisms of the overall multicomponent model, concluding with a discussion of the major contribution made by neuropsychological evidence to its development together with some suggestions as to comparative lack of influence from more recent studies based on neuro-imaging.